Electronic health literacy among older adults in the context of the COVID‐19 pandemic: A mixed‐methods study. (23rd May 2022) - Liu, Shuo; Wang, Xiao Qin; Yang, Bing Xiang; Luo, Dan; Liu, Yan; Fang, Xiao Juan; Ma, Simeng; Kang, Lijun; Huang, Hai‐Shan; Lu, Baili; Zhao, Jun; Liu, Zhongchun; et al.
Abstract: Aim: This study aimed to investigate eHealth literacy about coronavirus disease 2019 (COVID‐19) among older adults during the pandemic. Background: The COVID‐19 pandemic promoted the development of online health care. Higher demand for accessing information from the Internet was seen. Methods: This was a sequential explanatory mixed‐method study, involving a survey of older adults to explore the status and influencing factors of eHealth literacy regarding COVID‐19. Semi‐structured interviews were used to understand experiences and challenges regarding information retrieval, judgment and utilization. Results: A total of 337 older adults participated in the online questionnaire survey. Overall, older adults had slightly higher scores on eHealth literacy during the COVID‐19 pandemic. Participants' location in the past month and current health issues were associated with eHealth literacy. Qualitative data were collected from nine older adults and included that some older adults retrieved health‐related information during the pandemic. However, those who used non‐smartphones described difficulties in information retrieval. A glut of misinformation has resulted in an 'infodemic', which has not only increased the difficulty of judging information but also posed challenges in information utilization for older adults. Conclusion: Improving older adults' eHealth literacy is essential in promoting an improved response to major public health events and in providing better health care for this group in the future. It is essential that government health agencies and health care providers provide evidence‐based health information via social media platforms. Further efforts are needed to combine aspects of traditional and online health care services and provide reliable and updated online information and resources for older adults. Implications for Nursing Management: Providing evidence to eHealth literacy improvement and health management of older adults in the context of public health events.